2016
DOI: 10.1007/s00234-016-1733-7
|View full text |Cite
|
Sign up to set email alerts
|

Spinal dual-energy computed tomography: improved visualisation of spinal tumorous growth with a noise-optimised advanced monoenergetic post-processing algorithm

Abstract: MEI+ at low keV levels can significantly improve image quality and delineation of spinal growth in patients with portal-venous phase CT scans due to increased CNR and limited image noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…100 High-keV VMI reconstructions can also help reduce beam-hardening artefacts arising from deep brain stimulating electrodes. 101 Finally, a prior study demonstrated that dose reduction techniques can also be applied to DECT of the brain without a decrease in diagnostic performance for the detection of intracranial haemorrhage, 102 establishing DECT as dose-neutral for imaging of the brain.…”
Section: Bjr D'angelo Et Almentioning
confidence: 99%
“…100 High-keV VMI reconstructions can also help reduce beam-hardening artefacts arising from deep brain stimulating electrodes. 101 Finally, a prior study demonstrated that dose reduction techniques can also be applied to DECT of the brain without a decrease in diagnostic performance for the detection of intracranial haemorrhage, 102 establishing DECT as dose-neutral for imaging of the brain.…”
Section: Bjr D'angelo Et Almentioning
confidence: 99%
“…In all studies, the optimal energy levels for VMI+ reconstructions recommended by researchers for different tumors were typically in the range of 50-60 keV. The optimal energy levels of reconstruction recommended for various cancers/tumors are as follows: 50 keV for cutaneous malignant melanomas and renal cell carcinomas (RCCs) in the corticomedullary-phase of enhancement (19,20); 55 keV for head and neck cancers, lung cancers, and hypervascular liver tumors (21-23); 60 keV for RCCs in the nephrogenic-phase of enhancement, gastrointestinal stromal tumors, and abdominal metastases, and hypo-attenuating liver metastases from colorectal cancers (19,24,25); low energy levels especially 40 and 50 keV for pancreatic adenocarcinomas (26); and 40 keV (a small number of studies) for malignant tumors in the head and neck region, metastatic spinal tumors, and early gastric cancer (27)(28)(29)(30). Concerning head and neck malignancies, Albrecht et al found that 55 keV reconstructions could yield the best subjective image quality (21); however, May et al recommended 40 keV for optimal image quality (28).…”
Section: Tumormentioning
confidence: 99%